Role of wave coupling in the simulation of tropical storm Choi-wan (2021) using a coupled ocean-atmosphere model - Xia, Haofeng; Tang, Shuai; Chen, Jie; Du, Shengtao; Guo, Wuhong (Frontiers in Marine Science, 2025)
This study investigates the effects of wave coupling on the oceanic and atmospheric responses to Tropical Storm Choi-wan (2021) using a coupled ocean-atmosphere model. Modeled tropical cyclone metrics and ocean responses are compared with and without coupling ocean waves. A wave dependent surface roughness scheme is evaluated to understand the wave influence on tropical cyclone induced changes in sea surface temperature (SST), ocean currents, and wave fields. The results reveal that wave coupling significantly improves the representation of SST cooling and vertical ocean thermal structures. The wave dependent roughness scheme outperforms in capturing the cooling effect and ocean mixing processes induced by the storm. Wave-current coupling also impacts significant wave height distributions, particularly in storm-affected regions, where coupled simulations yield more realistic patterns compared to uncoupled runs. Furthermore, the inclusion of wave-current interactions enhances the accuracy of simulated ocean currents, reflecting the intensifications and directional changes caused by the storm. Overall, the wave dependent roughness parametrization demonstrated superior performance in reproducing storm-induced oceanic responses, emphasizing the critical role of wave coupling in simulating extreme weather events. This study underscores the importance of advanced coupled modeling systems in improving predictions of tropical cyclones and their impacts on the ocean and atmosphere.